Paleogeographie, structural and magmatic evidences for the existence of different lithospheric blocks in the Central Andes: samples from southern Peru and northern Chile - Carlotto Caillaux, Víctor Santiago (2005)
The Andes are classically considered to represent the type of orogenie chains resulting from the subduction of an oceanic plate beneath a continental plate. In spite of a considerable literature invoJving stratigraphie, paleogeographie, structural, magmatic and geophysical data, any model that convincingly ex plains the modality of the Andean surrection has been emerged. Ali the current models focused on the importance of the subducting plate and very few considerations on the heterogeneity of continental plate. Paleogeographie reconstructions, structural evidences and magmatic and metallogenic evolution of Southern Peruvian Western Cordillera and Northern Chi.lean Domeyko Cordillera are used to identify a structure that delineates two different lithospheric blocks.